Non-aqueous electrolyte and battery

By adding the compound shown in Structure Formula I to the nonaqueous electrolyte of the lithium battery to form a polymer film, the problem of destruction of the positive electrode material at high voltage is solved, the cycle life and energy density of the battery are significantly improved, and the cycle life and energy density of the battery are improved, and the polymer film is improved. The flame retardant properties of the electrolyte are obtained.

CN119419358AActive Publication Date: 2025-02-11SHENZHEN HIGHPOWER TECH CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411353299.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-26
Publication Date
2025-02-11
Estimated Expiration
2044-09-26

AI Technical Summary

Technical Problem

Lithium batteries are prone to damage to the positive electrode material at high voltages, resulting in transition metal dissolution and battery capacity attenuation.

Method used

A nonaqueous electrolyte is used, which includes a lithium salt, an organic solvent and a specific additive, which is a compound represented by structural formula I, which opens the ring polymerization on the surface of the positive electrode to form a film or passes through an acrylate group or a methyl group. Double bond polymerization of acrylate groups forms a polymer film, inhibiting the dissolution of transition metals and protecting the positive electrode material.

Benefits of technology

Suppress the dissolution of transition metal under high voltage environments, protect the positive electrode material, improve the cycle life and energy density of the battery, and improve the flame retardant performance of the electrolyte.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119419358A_ABST
    Figure CN119419358A_ABST
Patent Text Reader

Abstract

In order to solve the problem that a positive electrode material of an existing lithium battery is prone to being damaged under high voltage, the invention provides a non-aqueous electrolyte and a battery, the non-aqueous electrolyte comprises a lithium salt, an organic solvent and an additive, the additive comprises one or more of compounds shown in the structural formula I, the structural formula I is # imgabs0 #, R1 is selected from C or N, R2 is selected from C or N, and R3 is selected from H or H; r2 is selected from C, N or S; r3 is selected from a unit containing an acrylate group or a methacrylate group; r < 4 >, R < 5 > and R < 6 > are respectively and independently selected from substituted or unsubstituted C1-C8 alkyl groups, substituted or unsubstituted C2-C8 alkenyl groups, H or halogen.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of batteries, and in particular relates to a non-aqueous electrolyte and a battery. Background Art

[0002] Lithium batteries have been increasingly widely used in household appliances, portable electronic devices, and electric vehicles due to their high energy density and high voltage. In recent years, with the continuous development of lithium-ion battery technology, high operating voltage, long cycle life, and high safety have become important performance indicators of lithium-ion batteries. However, excessively high operating voltage in lithium batteries will intensify the side reactions between the positive electrode active material and the electrolyte, causing damage to the positive electrode material, leading to a large amount of dissolution of transition metals, causing battery capacity decay, and further affecting the battery's cycle performance. Therefore, how to make lithium batteries operate stably at high voltage is the focus of lithium battery research. Summary of the invention

[0003] In view of the problem that the positive electrode material of the existing lithium battery is easily damaged under high voltage, the present invention provides a non-aqueous electrolyte and a battery.

[0004] The technical solution adopted by the present invention to solve the above technical problems is as follows: In one aspect, the present invention provides a non-aqueous electrolyte, comprising a lithium salt, an organic solvent and an additive, wherein the additive comprises one or more compounds represented by structural formula I. The structural formula I is , Wherein, the R1 is selected from C or N; the R2 is selected from C, N or S; the R3 is selected from a unit containing an acrylate group or a methacrylate group; and the R4, R5, and R6 are each independently selected from a substituted or unsubstituted C1~C8 alkyl, a substituted or unsubstituted C2~C8 alkenyl, H, hydroxyl or halogen.

[0005] Optionally, the mass content of the substance of structural formula I in the non-aqueous electrolyte is 0.5%~8%.

[0006] Optionally, the mass content of the substance of structural formula I in the non-aqueous electrolyte is 2% to 5%.

[0007] Optionally, the substance of structural formula I includes one or more of structural formulas I-1 to I-6, .

[0008] Optionally, the additive further comprises a nitrile additive and fluoroethylene carbonate, and the nitrile additive comprises at least one of a C4-C10 dinitrile or a C8-C12 trinitrile.

[0009] Optionally, the nitrile additive includes one or more of succinonitrile, adiponitrile, glutaronitrile, suberonitrile, sebaconitrile, 1,3,5-pentanetricarboxynitrile and hexanetrinitrile.

[0010] Optionally, the mass content of the nitrile additive in the non-aqueous electrolyte is 0.1% to 5%; And / or, the mass content of the fluoroethylene carbonate in the non-aqueous electrolyte is 0.1% to 10%.

[0011] Optionally, the lithium salt further comprises one or more of lithium hexafluorophosphate, lithium difluorooxalatoborate, lithium tetrafluoroborate, lithium bis(trifluoromethylsulfonyl)imide, lithium bis(fluorosulfonyl)imide, and lithium bis(oxalatoborate); And / or, the concentration of the lithium salt is 0.5M~2.0M.

[0012] Optionally, the organic solvent includes at least two of ethylene carbonate, propylene carbonate, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, ethyl propionate, propyl propionate, methyl propionate, ethyl acetate, fluoroethyl acetate, fluoroethyl methyl carbonate, fluorodimethyl carbonate, and fluoropropylene carbonate.

[0013] In another aspect, the present invention provides a battery comprising a positive electrode sheet, a negative electrode sheet, a separator and the non-aqueous electrolyte as described in any one of the above.

[0014] Optionally, the positive electrode sheet includes a positive electrode active material, and the positive electrode active material includes one or more of lithium cobalt oxide, lithium nickel cobalt manganese oxide, lithium iron phosphate, lithium iron manganese phosphate, and lithium manganese oxide; The negative electrode sheet includes a negative electrode active material, and the negative electrode active material includes natural graphite, artificial graphite, mesophase micro carbon beads, hard carbon, soft carbon, silicon, silicon oxide, silicon-carbon composite, Li-Sn alloy, Li-Sn-O alloy, Sn, SnO, SnO2, TiO2-Li4Ti5O 12 and one or more of Li-Al alloys.

[0015] In the present invention, the compound shown in structural formula I in the non-aqueous electrolyte forms a film on the surface of the positive electrode by ring-opening polymerization, or forms a polymer film on the surface of the positive electrode by double bond polymerization of acrylate or methacrylate groups, so that the non-aqueous electrolyte inhibits the dissolution of transition metals under high voltage environment, protects the positive electrode material from being destroyed, thereby improving the cycle life of the battery and the energy density of the battery. At the same time, the phosphoric acid group in the compound shown in structural formula I can capture hydroxyl groups and hydrogen protons, thereby improving the flame retardant properties of the non-aqueous electrolyte. DETAILED DESCRIPTION In order to make the technical problems, technical solutions and beneficial effects solved by the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0016] One embodiment of the present invention provides a non-aqueous electrolyte, including a lithium salt, an organic solvent and an additive, wherein the additive includes one or more compounds represented by structural formula I. The structural formula I is , Wherein, the R1 is selected from C or N; the R2 is selected from C, N or S; the R3 is selected from a unit containing an acrylate group or a methacrylate group; and the R4, R5, and R6 are each independently selected from a substituted or unsubstituted C1~C8 alkyl, a substituted or unsubstituted C2~C8 alkenyl, H, hydroxyl or halogen.

[0017] In the present invention, the compound shown in structural formula I in the non-aqueous electrolyte forms a film on the surface of the positive electrode by ring-opening polymerization, or forms a polymer film on the surface of the positive electrode by double bond polymerization of acrylate or methacrylate groups, so that the non-aqueous electrolyte inhibits the dissolution of transition metals under high voltage environment, protects the positive electrode material from being destroyed, thereby improving the cycle life of the battery and the energy density of the battery. At the same time, the phosphoric acid group in the compound shown in structural formula I can capture hydroxyl groups and hydrogen protons, thereby improving the flame retardant properties of the non-aqueous electrolyte. In some embodiments, the mass content of the substance of structural formula I in the non-aqueous electrolyte is 0.5% to 8%. The electrolyte containing the substance of structural formula I that meets the above content range can improve the high temperature and high pressure performance and safety performance of the battery cell, reduce impedance, and increase the cycle life of the battery.

[0018] In a specific embodiment, the mass content of the substance of structural formula I includes but is not limited to 0.5%, 0.8%, 1.1%, 1.4%, 1.7%, 2%, 2.3%, 2.6%, 2.9%, 3.2%, 3.5%, 3.8%, 4.1%, 4.4%, 4.7%, 5%, 5.5%, 6%, 6.5%, 7%, 7.5% or 8%.

[0019] In a preferred embodiment, the mass content of the substance of structural formula I in the non-aqueous electrolyte is 2% to 5%. The non-aqueous electrolyte containing the substance of structural formula I that meets the above content range can further improve the high temperature and high pressure performance and safety performance of the battery and increase the cycle life of the battery.

[0020] In some embodiments, the substance of formula I includes one or more of formulas I-1 to I-6, .

[0021] By selecting the above-mentioned additives, the high temperature and high pressure performance and safety performance of the battery cell can be further improved, and the flame retardant performance of the electrolyte can be improved.

[0022] Furthermore, the preparation method of the substance of formula I-1 comprises the following steps: 2,4-dihydroxypyridine, acrylic acid, hypophosphorous acid are used as raw materials, and triethylamine is used as a catalyst. 2,4-dihydroxypyridine is mixed with an equal amount of triethylamine, and stirred to obtain a mixed solution. Acrylic acid is slowly added dropwise to the mixed solution at a certain reaction temperature, and hypophosphorous acid is slowly added dropwise after the addition is completed, and stirred at a uniform speed. After the addition is completed, stirring is continued at room temperature for 5 hours, and the reactant is filtered to obtain the substance shown in formula I-1.

[0023] The preparation method of the substance of structural formula I-2 comprises the following steps: 2,4-dihydroxypyridine, acrylic acid, and difluorophosphoric acid are used as raw materials, and triethylamine is used as a catalyst. 2,4-dihydroxypyridine is mixed with an equal amount of triethylamine, and stirred to obtain a mixed solution. Acrylic acid is slowly added dropwise to the mixed solution at a certain reaction temperature, and then difluorophosphoric acid is slowly added dropwise after the addition is completed, and stirred at a uniform speed. After the addition is completed, stirring is continued at room temperature for 5 hours, and the reactant is filtered to obtain the substance shown in formula I-2.

[0024] The preparation method of the substance of structural formula I-3 comprises the following steps: 2,4-dihydroxypyridine, acrylic acid, monofluorophosphoric acid are used as raw materials, and triethylamine is used as a catalyst. 2,4-dihydroxypyridine is mixed with an equal amount of triethylamine, and stirred to obtain a mixed solution. Acrylic acid is slowly added dropwise to the mixed solution at a certain reaction temperature, and then monofluorophosphoric acid is slowly added dropwise after the addition is completed, and stirred at a uniform speed. After the addition is completed, stirring is continued at room temperature for 5 hours, and the reactant is filtered to obtain the substance shown in formula I-3.

[0025] The preparation method of the substance of structural formula I-4 comprises the following steps: 2,4-dihydroxypyridine, acrylic acid, and dimethylphosphonic acid are used as raw materials, and triethylamine is used as a catalyst. 2,4-dihydroxypyridine is mixed with an equal amount of triethylamine, and stirred to obtain a mixed solution. Acrylic acid is slowly added dropwise to the mixed solution at a certain reaction temperature, and then dimethylphosphonic acid is slowly added dropwise after the addition is completed, and stirred at a uniform speed. After the addition is completed, stirring is continued at room temperature for 5 hours, and the reactant is filtered to obtain the substance shown in formula I-4.

[0026] The preparation method of the substance of structural formula I-5 comprises the following steps: 2,4-dihydroxypyridine, methacrylic acid, and dimethylphosphonic acid are used as raw materials, and triethylamine is used as a catalyst. 2,4-dihydroxypyridine is mixed with an equal amount of triethylamine, and stirred to obtain a mixed solution. Methacrylic acid is slowly added dropwise to the mixed solution at a certain reaction temperature, and then dimethylphosphonic acid is slowly added dropwise after the addition is completed, and stirred at a uniform speed. After the addition is completed, stirring is continued at room temperature for 5 hours, and the reactant is filtered to obtain the substance shown in Ⅰ-5.

[0027] The preparation method of the substance of structural formula I-6 comprises the following steps: 2,4-dihydroxypyridine, methacrylic acid, and diethylphosphonic acid are used as raw materials, and triethylamine is used as a catalyst. 2,4-dihydroxypyridine is mixed with an equal amount of triethylamine, and stirred to obtain a mixed solution. Methacrylic acid is slowly added dropwise to the mixed solution at a certain reaction temperature, and then diethylphosphonic acid is slowly added dropwise after the addition is completed, and stirred at a uniform speed. After the addition is completed, stirring is continued at room temperature for 5 hours, and the reactant is filtered to obtain the substance shown in Ⅰ-6.

[0028] In some embodiments, the additive also includes a nitrile additive and fluoroethylene carbonate, and the nitrile additive includes at least one of a dinitrile of C4~C10 or a trinitrile of C8~C12. By adding a nitrile additive to the non-aqueous electrolyte, it is convenient to form a film at the positive electrode, and the positive electrode is further protected. By adding fluoroethylene carbonate, a LiF-rich SEI is formed at the negative electrode to further protect the negative electrode. The nitrile additive, fluoroethylene carbonate and the substance of structural formula I are used in combination to better protect the positive and negative electrodes, improve the cycle performance of the battery under high voltage, and enhance the energy density of the battery.

[0029] In some embodiments, the nitrile additive includes one or more of succinonitrile (SN), adiponitrile (ADN), glutaronitrile, suberonitrile, sebaconitrile, 1,3,5-pentanetricarboxynitrile, and hexanetricarbonitrile (HTCN). By selecting the above nitrile additives, it is easy to form a film on the positive electrode, avoid side reactions between the positive electrode and the electrolyte, improve the stability of the electrolyte, and further protect the positive electrode.

[0030] In some embodiments, the mass content of the nitrile additive in the non-aqueous electrolyte is 0.1% to 5%.

[0031] The mass content of the fluoroethylene carbonate in the non-aqueous electrolyte is 0.1% to 10%.

[0032] By regulating the content of nitrile additives and fluoroethylene carbonate, the occurrence of side reactions in the electrolyte during the charging and discharging process can be inhibited, the positive and negative electrodes can be better protected, the cycle performance of the battery under high voltage can be improved, and the energy density of the battery can be increased.

[0033] In a specific embodiment, the content of the nitrile additive includes, but is not limited to, 0.1%, 1%, 2%, 3%, 3.5%, 4%, 4.5% or 5%. The mass content of fluoroethylene carbonate includes, but is not limited to, 0.1%, 1%, 2%, 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, 7%, 8%, 9% or 10%.

[0034] In some embodiments, the lithium salt further comprises one or more of lithium hexafluorophosphate (LiPF6), lithium difluorooxalatoborate (LiODFB), lithium tetrafluoroborate (LiBF4), lithium bis(trifluoromethylsulfonyl)imide (LiTFSI), lithium bis(fluorosulfonyl)imide (LiFSI), and lithium bis(oxalatoborate) (LiBOB). By selecting the above ionizable lithium salts, the amount of lithium ions that can migrate in the electrolyte is guaranteed.

[0035] In some embodiments, the concentration of the lithium salt is 0.5 M to 2.0 M. The concentration of the lithium salt in the electrolyte is not particularly limited, but when the content of the lithium salt is lower than 0.5 M, the number of mobile lithium ions in the electrolyte is insufficient, and when the content of the lithium salt is higher than 2 M, the viscosity of the electrolyte may increase, resulting in an increase in the impedance of the electrolyte, which reduces the migration rate of lithium ions and may reduce the performance of the battery.

[0036] In some embodiments, the organic solvent includes at least two of ethylene carbonate (EC), propylene carbonate (PC), dimethyl carbonate (DMC), diethyl carbonate (DEC), ethyl methyl carbonate (EMC), ethyl propionate (EP), propyl propionate (PP), methyl propionate (MP), ethyl acetate (EA), fluoroethyl acetate (DFEA), fluoroethyl methyl carbonate (FEMC), fluorodimethyl carbonate (FDMC), and fluoropropylene carbonate (FPC).

[0037] Taking the mass of the non-aqueous electrolyte as 100%, the content of the organic solvent is 70% to 90%. The viscosity of the electrolyte is improved by adjusting the content of the organic solvent to ensure the migration rate of lithium ions in the electrolyte.

[0038] In a specific embodiment, the content of the organic solvent is 70%, 75%, 80%, 85% or 90%.

[0039] On the other hand, an embodiment of the present invention provides a battery, including a positive electrode sheet, a negative electrode sheet, a separator and a non-aqueous electrolyte as described in any one of the above embodiments. By selecting the non-aqueous electrolyte described in the above embodiment, the positive and negative electrodes of the battery working at a high voltage are protected, and side reactions between the positive electrode and the wastewater electrolyte are avoided, thereby improving the cycle life and energy density of the battery.

[0040] In some embodiments, the positive electrode sheet includes a positive electrode active material, and the positive electrode active material includes one or more of lithium cobalt oxide, lithium nickel cobalt manganese oxide, lithium iron phosphate, lithium iron manganese phosphate, and lithium manganese oxide; The negative electrode sheet includes a negative electrode active material, and the negative electrode active material includes natural graphite, artificial graphite, mesophase micro carbon beads, hard carbon, soft carbon, silicon, silicon oxide, silicon-carbon composite, Li-Sn alloy, Li-Sn-O alloy, Sn, SnO, SnO2, TiO2-Li4Ti5O 12 and one or more of Li-Al alloys.

[0041] The present invention is further described below by way of examples.

[0042] Example 1 This embodiment is used to illustrate the non-aqueous electrolyte and battery disclosed in the present invention, and includes the following operating steps: Preparation of non-aqueous electrolyte EC / PC / DEC / PP were mixed at a ratio of 1:1:1:1 in a glove box with water and oxygen content <10 ppm, and 1 M LiPF6, 2% additive of structural formula I-1, 2% HTCN and 5% FEC were added to obtain a non-aqueous electrolyte. Production of positive electrode: The positive electrode active material lithium cobalt oxide, conductive agent CNT, and adhesive PVDF are fully stirred and mixed in NMP solvent at a weight ratio of 97:1.5:1.5, and the slurry is coated on aluminum foil. After drying, cold pressing, stripping, sheeting, welding of pole ears, and gluing, a positive electrode sheet that meets the requirements is made. Other positive electrode materials such as lithium manganese oxide (LiMn2O4), 532 ternary (LiNi 0.5 Co 0.3 Mn 0.2 ) were prepared in a similar manner.

[0043] Negative electrode production: The negative electrode active material graphite, conductive agent SP, thickener CMC, and adhesive SBR are mixed in a proper amount of deionized water solvent at a mass ratio of 96.3:1:1.2:1.5 to form a uniform negative electrode slurry. The slurry is applied to the negative electrode current collector copper foil, and then dried, cold pressed, stripped, sheeted, welded to the pole ear, and glued to form a negative electrode sheet that meets the requirements. Other negative electrode materials such as lithium titanate are prepared in a similar way.

[0044] Lithium-ion battery production: The positive electrode sheet, separator and negative electrode sheet are wound / stacked to obtain a bare cell. The bare cell is placed in the aluminum-plastic film that has been punched out to complete the top and side sealing. After high-temperature baking, liquid injection, static, formation, capacity division, testing and other processes, the battery is completed.

[0045] Example 2-23 The examples are used to illustrate the non-aqueous electrolyte and battery disclosed in the present invention, and include most of the operating steps in Example 1, except that the formulation in Table 1 is used.

[0046] Comparative Examples 1-3 The comparative example is used to compare and illustrate the non-aqueous electrolyte and battery disclosed in the present invention, and includes most of the operating steps in Example 1, except that the formula in Table 1 is used.

[0047] Table 1 Performance Testing 1. The lithium-ion batteries prepared in the above examples and comparative examples were subjected to the following performance tests: Test 1: Charge to 4.53V at 1C constant current and constant voltage at 25℃, cut-off current 0.05C, let stand for 10min, discharge to 3.0V at 1C, record discharge capacity C0 as initial capacity, repeat 800 cycles. The final capacity C of 800 cycles is 800 , then the capacity retention rate = C 800 / C0.

[0048] Test 2: Charge to 4.53V at 0.5C constant current and constant voltage at 45℃, cut-off current 0.05C, let stand for 10min, discharge to 3.0V at 0.5C, record discharge capacity C0 as initial capacity, repeat 500 cycles. The final capacity C of 500 cycles is 500 , then the capacity retention rate = C 500 / C0.

[0049] The test results are shown in Table 2.

[0050] Table 2 It can be seen from the test results in Table 2 that the embodiment of the present invention can significantly improve the room temperature cycle performance and high temperature cycle performance of the lithium ion battery under high voltage by adding the non-aqueous electrolyte to the lithium ion battery.

[0051] It can be seen from the test results of Examples 1-6 and Comparative Example 1 that the degree of improvement of the room temperature and high temperature cycle performance of lithium ion batteries by the substances of formula I with different structures is different, but it is significantly better than Comparative Example 1 without the addition of the substance of formula I. In combination with Examples 1 and 7-21, it can be found that the content of the substance of formula I, the type and content of nitrile additives, and the content of FEC will also affect the cycle performance of the battery to varying degrees. And it can be found from Examples 1 and 7-11 that too low or too high content of the substance of formula I is not conducive to the improvement of the cycle performance. The content of the substance of formula I is too low, and the protection of the positive electrode side is not enough, so that the capacity decay is faster. If the content of the substance of formula I is too high, the internal impedance of the battery will be large, and the cycle performance of the battery will also be deteriorated. If the content of nitrile additives is too high, the internal impedance of the battery will be too large, which is not conducive to the cycle performance of the battery. If the content is too low, the protective effect on the positive electrode is not enough, causing the transition metal to dissolve and deposit at the negative electrode, which will also deteriorate the cycle of the battery. If the content of fluoroethylene carbonate is too high, it will cause serious gas production inside the battery cell. If the content is too low, the SEI will be unstable and it will also cause faster cycle attenuation.

[0052] In combination with Example 1, Example 16, Example 20, Example 22 and Comparative Examples 1-3, it can be seen that the use of nitrile additives, fluoroethylene carbonate and the substance of structural formula I can better protect the positive and negative electrodes, improve the cycle performance of the battery under high voltage, and enhance the energy density of the battery.

[0053] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A non-aqueous electrolyte, characterized in that: It includes a lithium salt, an organic solvent and an additive, wherein the additive includes one or more compounds shown in structural formula I, wherein structural formula I is , Wherein, the R1 is selected from C or N; the R2 is selected from C, N or S; the R3 is selected from a unit containing an acrylate group or a methacrylate group; and the R4, R5, and R6 are each independently selected from a substituted or unsubstituted C1~C8 alkyl, a substituted or unsubstituted C2~C8 alkenyl, H, hydroxyl or halogen.

2. The non-aqueous electrolyte according to claim 1, characterized in that The mass content of the substance of structural formula I in the non-aqueous electrolyte is 0.5% to 8%.

3. The non-aqueous electrolyte according to claim 1, characterized in that The mass content of the substance of structural formula I in the non-aqueous electrolyte is 2% to 5%.

4. The non-aqueous electrolyte according to any one of claims 1 to 3, characterized in that: The substance of structural formula I includes one or more of structural formulas I-1 to I-6, 。 5. The non-aqueous electrolyte according to claim 1, characterized in that The additives further include nitrile additives and fluoroethylene carbonate, wherein the nitrile additives include at least one of C4-C10 dinitriles or C8-C12 trinitriles.

6. The non-aqueous electrolyte according to claim 5, characterized in that The nitrile additive includes one or more of succinonitrile, adiponitrile, glutaronitrile, suberonitrile, sebaconitrile, 1,3,5-pentanetricarboxynitrile and hexanetrinitrile.

7. The non-aqueous electrolyte according to claim 5, characterized in that The mass content of the nitrile additive in the non-aqueous electrolyte is 0.1% to 5%; And / or, the mass content of the fluoroethylene carbonate in the non-aqueous electrolyte is 0.1% to 10%.

8. The non-aqueous electrolyte according to claim 1, characterized in that The lithium salt further comprises one or more of lithium hexafluorophosphate, lithium difluorooxalatoborate, lithium tetrafluoroborate, lithium bis(trifluoromethylsulfonyl)imide, lithium bis(fluorosulfonyl)imide, and lithium bis(oxalatoborate); And / or, the concentration of the lithium salt is 0.5M~2.0M; And / or, the organic solvent includes at least two of ethylene carbonate, propylene carbonate, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, ethyl propionate, propyl propionate, methyl propionate, ethyl acetate, fluoroethyl acetate, fluoroethyl methyl carbonate, fluorodimethyl carbonate, and fluoropropylene carbonate.

9. A battery, characterized in that: The invention comprises a positive electrode sheet, a negative electrode sheet, a separator and the non-aqueous electrolyte according to any one of claims 1 to 8.

10. The battery according to claim 9, characterized in that The positive electrode sheet includes a positive electrode active material, and the positive electrode active material includes one or more of lithium cobalt oxide, lithium nickel cobalt manganese oxide, lithium iron phosphate, lithium iron manganese phosphate, and lithium manganese oxide; The negative electrode sheet includes a negative electrode active material, and the negative electrode active material includes natural graphite, artificial graphite, mesophase micro carbon beads, hard carbon, soft carbon, silicon, silicon oxide, silicon-carbon composite, Li-Sn alloy, Li-Sn-O alloy, Sn, SnO, SnO2, TiO2-Li4Ti5O 12 and one or more of Li-Al alloys.

Citation Information

Patent Citations

  • Polymer electrolyte and preparation method and application thereof

    CN112979875A

  • Non-aqueous electrolyte and lithium secondary battery including the same

    CN113497272A

  • Electrolyte additive, non-aqueous electrolyte and lithium ion battery

    CN114552011A

  • Lithium ion battery

    CN117525583A

  • Lithium ion battery non-aqueous electrolyte and lithium ion battery

    CN117747947A